If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 1 = 7 + 3x Reorder the terms: 1 + 5x = 7 + 3x Solving 1 + 5x = 7 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 1 + 5x + -3x = 7 + 3x + -3x Combine like terms: 5x + -3x = 2x 1 + 2x = 7 + 3x + -3x Combine like terms: 3x + -3x = 0 1 + 2x = 7 + 0 1 + 2x = 7 Add '-1' to each side of the equation. 1 + -1 + 2x = 7 + -1 Combine like terms: 1 + -1 = 0 0 + 2x = 7 + -1 2x = 7 + -1 Combine like terms: 7 + -1 = 6 2x = 6 Divide each side by '2'. x = 3 Simplifying x = 3
| 160=-7x-6(2x+5) | | 4(5x+7)+-8=-16 | | 3(x-1)=3x+2 | | 8x+8=8x+12 | | 4r+15=4r+11 | | 4xy*6xy= | | -2(4x+5)-11=-5 | | 2x-2=x+x | | 23x-8-14x=10 | | 2(b+8)-9=9 | | 2x^2=-144 | | 3k^2-11k-20=0 | | (8x^3)(2)= | | -8b+9+6b=3b+14 | | (4xy)(6xy)= | | 1+7=43+x | | 234x-67=56 | | y-2=y+3 | | 4(5x-7)-8x=-5 | | 4xy+6xy= | | 6x+24=12x+14 | | 6x-(4x+7)= | | 5a+4(2a+4)= | | 3y-9y=102 | | 344x-78=78 | | 3x^2+3=6x | | 1. 3+8x+7=34 | | 2345x=567 | | 2345x-567=567 | | (x+3)2=(x+5)3 | | 4t^4+8-(3t^4+5)= | | x+5=x+(9-x) |